Національний ботанічний сад ім. М.М. Гришка: досягнення і перспективи розвитку наукових досліджень у ХХІ ст. - Zaimenko, N.V.; Moroz, P.A.; Gaponenko, M.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The history of creation and development of M.M. Gryshko National Botanical Gardens of the NAS of Uk raine, their structure, principles of laying out, plots and collections are submitted. It is told about directions of scientific researches, structure of a garden, and also about scientific achievements in the field of protection of plants, introduction, selections, green construction, space biology, allelopathy, medical botany and bioindication. Prospects of development of scientific researches NBG in ХХІ century are outlined.